2018
DOI: 10.1111/nph.15146
|View full text |Cite
|
Sign up to set email alerts
|

Zinc isotope fractionation during grain filling of wheat and a comparison of zinc and cadmium isotope ratios in identical soil–plant systems

Abstract: Remobilization of zinc (Zn) from shoot to grain contributes significantly to Zn grain concentrations and thereby to food quality. On the other hand, strong accumulation of cadmium (Cd) in grain is detrimental for food quality. Zinc concentrations and isotope ratios were measured in wheat shoots (Triticum aestivum) at different growth stages to elucidate Zn pathways and processes in the shoot during grain filling. Zinc mass significantly decreased while heavy Zn isotopes accumulated in straw during grain fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 57 publications
10
31
1
Order By: Relevance
“…If correct, this would indicate that Cd complexation by thiol groups may be associated with little or no Cd isotope fractionation. This conclusion stands in contrast to previous investigations, which suggested that Cd-thiol complexes preferentially bind isotopically light Cd 40 .…”
Section: Role Of Metal Transporters In Response To CD Exposure In Cacaocontrasting
confidence: 99%
See 1 more Smart Citation
“…If correct, this would indicate that Cd complexation by thiol groups may be associated with little or no Cd isotope fractionation. This conclusion stands in contrast to previous investigations, which suggested that Cd-thiol complexes preferentially bind isotopically light Cd 40 .…”
Section: Role Of Metal Transporters In Response To CD Exposure In Cacaocontrasting
confidence: 99%
“…An alternative, and more likely, scenario is that different plant groups utilise several similar transporters for Cd uptake. Each transporter thereby imparts a characteristic isotopic signal during Cd handling, and this could vary from preferred transport of light Cd isotopes to little or even positive Cd isotope fractionation, if the transporters feature different metal coordination environments 34,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased mobility of Zn over Cd in the shoot is either related to selective membrane transport in the shoot or to the storage forms of both elements. In contrast to Cd, light Zn isotopes accumulated in rice and wheat ( Arnold et al, 2015 ; Wiggenhauser et al, 2018 ), which in indicates that combined speciation and isotope analyses could provide novel insights into the processes that separate Cd from Zn. Currently, the interplay of Cd storage forms/Cd speciation and membrane transporters are not well understood.…”
Section: Implications and Outlookmentioning
confidence: 99%
“…58 These contrasting observations may reect that Zn, as an essential micronutrient, is intensively translocated within plants via the phloem whilst such translocation is expected to be less important for non-essential Cd. 59 The cacao beans feature more complex Cd isotope systematics. At Farms B and C, the Nacional beans display the lowest (Tables 2 and 3).…”
Section: Distribution and Isotope Fractionation In The Cacao Tissuesmentioning
confidence: 99%